2022
DOI: 10.1128/spectrum.01593-22
|View full text |Cite
|
Sign up to set email alerts
|

Different Characteristics in Gut Microbiome between Advanced Adenoma Patients and Colorectal Cancer Patients by Metagenomic Analysis

Abstract: There are differences in characteristic microorganisms between AA and CRC. However, current studies have indicated that bacteriological analysis cannot identify CC from AA, and thus, we wondered if there were some other targets that could be used to identify CRC from AA in the gut microbiome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…and Oscillibacter spp. are decreased in colorectal cancer and inflammatory bowel disease (IBD) owing to the gut [ [37] , [38] , [39] , [40] ]. Hence, the lung microbiome alterations found in this study suggest the destruction of the mucin layer and inflammation in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…and Oscillibacter spp. are decreased in colorectal cancer and inflammatory bowel disease (IBD) owing to the gut [ [37] , [38] , [39] , [40] ]. Hence, the lung microbiome alterations found in this study suggest the destruction of the mucin layer and inflammation in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported reduced levels of Blautia spp. in the fecal microbiome of CRC patients compared to healthy controls [ 66 , 67 , 68 ]. Wang et al reported a decrease in the abundance of Lachnoclostridium sp.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that Blastocystis and Entamoeba were significantly positively correlated with various methanogenic archaea. The possible use of methanogens as probiotics has received particular attention in humans [ 40 , 41 ]; therefore, the positive relationship between Blastocystis , Entamoeba , and methanogenic archaea may be beneficial for gut health. The relationship between archaea and parasites in animals has received little attention, and more research is needed to uncover this phenomenon.…”
Section: Discussionmentioning
confidence: 99%